2017
DOI: 10.2147/dddt.s129913
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 siRNA can reduce damage to retinal cells induced by high glucose in vitro and in vivo

Abstract: BackgroundDiabetic retinopathy (DR), one of the most common complications of late-phase diabetes, is associated with many risk factors, among which continuous low-grade inflammation is one of the principal ones. As such, lowering inflammation levels and maintain the viability of human retinal endothelial cells (HRECs) are critical for DR therapy. HMGB1 is a well-known proinflammatory cytokine. However, whether HMGB1 small interfering RNA (siRNA) can protect retina cells under a high-glucose environment from mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 30 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…HMGB1 suppression, mediated by intravitreal injections of siRNA, is capable, in diabetic rats, of reducing retinal apoptosis rates as well as improving retinal function. In HRECs exposed to high glucose concentrations, siRNA HMGB1 improved cell viability and reduced the oxidative damage lowering ROS production [105]. The same study group demonstrated the protective role of HMGB1 inhibition in murine DR models.…”
Section: Smallmentioning
confidence: 77%
“…HMGB1 suppression, mediated by intravitreal injections of siRNA, is capable, in diabetic rats, of reducing retinal apoptosis rates as well as improving retinal function. In HRECs exposed to high glucose concentrations, siRNA HMGB1 improved cell viability and reduced the oxidative damage lowering ROS production [105]. The same study group demonstrated the protective role of HMGB1 inhibition in murine DR models.…”
Section: Smallmentioning
confidence: 77%
“…Inhibition of HMGB1 could be developed as a therapy for diabetic disease. HMGB1 siRNA improved electroretinogram (ERG) measurements, retinal morphology, and reduced retinal cell apoptosis when given intravitreally to diabetic rats or REC grown in high glucose (Jiang and Chen 2017 [33]). Studies in ARPE-19 cells demonstrated that HMGB1 upregulated angiogenic and fibrogenic factors in response to hypoxia (Chang et al 2017 [34]).…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that HMGB1 induced cleaved caspase-3, IL-1β and PARP-1, and that this effect is inhibited by administration of GA. Interestingly, in a work by Sohn and coworkers, the administration in diabetic rats of extract of Polygonum cuspidatum (PCE), a dried root with anti-inflammatory action, reduced HMGB1, RAGE and NF-kB expression and it ameliorated vascular retinal permeability, inhibiting tight junction leakage [133]. To support evidences of HMGB1 activity on progression of DR, Jiang and coworkers demonstrated that intravitreal injection of HMGB1 siRNA in rats reduced retinal damage and cellular death and it improved retinal function [135]. Furthermore, in human retinal endothelial cells treated with high glucose, HMGB1siRNA reduced oxidative stress and cellular apoptosis.…”
Section: Hmgb1 and Diabetic Retinopathymentioning
confidence: 99%